Nucleoside supplements as treatments for mitochondrial DNA depletion syndrome - Dombi, Eszter; Marinaki, Tony; Spingardi, Paolo; Millar, Val; Hadjichristou, Nastasia; Carver, Janet; Johnston, Iain G.; Fratter, Carl; Poulton, Joanna (Frontiers in Cell and Developmental Biology, 2024)
Nucleoside therapy is a promising treatment. Patients with mitochondrial DNA depletion syndrome (MDS), due to thymidine kinase 2 mutations, are supplemented with deoxy-pyrimidines. Previous studies have shown that supplementing polymerase gamma and deoxyguanosine kinase deficient myotubes with deoxy-nucleoside monophosphates increased mitochondrial DNA (mtDNA) copy numbers in vitro. We aimed to study the effects of different combinations of nucleosides in MDS patients. Therefore, we used fibroblasts harbouring mutations in POLG, DGUOK or TWNK (genes encoding alpha subunit of mtDNA gamma polymerase, deoxyguanosine kinase and Twinkle MtDNA Helicase respectively) to model the effects of 15 combinations of nucleosides, making this the most comprehensive cell-based study currently. Using high content imaging, we measured the effects of supplements at the single-cell level on mitochondrial membrane potential, cell numbers and mtDNA content. We show that high concentrations of nucleoside combinations (200 µM), that increase mtDNA content, impair cell growth. This was alleviated by lowering the concentration to 50 µM. Furthermore, a combination of all four deoxynucleosides (ATGC) increased mtDNA content of POLG, TWNK and DGUOK quiescent fibroblasts, and significantly increased mtDNA recovery following artificial depletion using ddC. Both POLG derived replicating cell cultures benefited (effects on mitochondrial growth, membrane potential and mtDNA content) from C and T supplements, suggesting that this combination could be explored further for the treatment of POLG patients.